Bluegrass paradise : Royal Spring and the birth of Georgetown, Kentucky - O'Dell, Gary A. (The University Press of Kentucky, 2023)
"Much of Kentucky is underlain by carbonate rocks, mainly limestone, which has produced a topography known as karst, characterized by caves, sinking streams, and numerous springs of cool, clear water. Spring water has long been viewed as the purest sort of water. In the latter part of the eighteenth century, as settlers came into the region, lands were selected and surveyed with two priorities in mind: the fertility of the soil and the presence of a copious fresh-water spring. These two features were perceived sufficient for the needs of homesteads and communities. Thus, the pattern of pioneer settlement was largely determined by the locations of suitable springs. In Bluegrass Paradise: The Royal Spring of Georgetown, Kentucky, Gary A. O'Dell tells the story of the Royal Spring, the largest spring in central Kentucky. The spring is the reason the site of Georgetown was chosen during the pioneer settlement era in order to assure the inhabitants a supply of pure water. For nearly 250 years, the Royal Spring has faithfully served the water needs of the community of Georgetown, and today the locale is a cherished cultural and historical asset that provides greenspace within a rapidly growing city. Over two and a half centuries as a community water supply, stewardship of the Royal Spring and its riparian corridor has been inconstant. For the first century after settlement, the spring area served as a grassy commons enjoyed by the citizenry, but in the latter part of the nineteenth century it was transformed into an industrial wasteland and dumping ground for rubbish. Generations of artists, ignoring the blighted landscape surrounding the spring, were nevertheless inspired to render the springhead as a tranquil romantic setting, nature at its finest. Lastly, it has been the focus of a century-long effort at remediation intended to transform the neglected area into a serene oasis for contemplation, recreation and community activities, a sorely needed city greenspace and park. Today, the spring is regarded and protected as a priceless natural resource and an historic and cultural asset for Georgetown"--